ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KEPUASAN PELANGGAN - Brilian, Sukma Catur; Haris, Murwanto (Fakultas Ekonomi, Universitas Semarang, 2023)
This study aims to analyze the factors that affected customer satisfaction at CV. Syailendra Elektronik specifically with service quality, price and brand image. The population in this study are all customers of CV. Syailendra Electronics Semarang. The sample in this study amounted to 96 respondents who were selected using a purposive sampling technique. Data collection techniques in this study using a questionnaire. The data analysis technique in this study used multiple linear regression analysis with the help of SPSS. The results of this study found that customer satisfaction at CV. Syailendra Elektronik was influenced positively and significantly by the service quality factor of 0.309, the price factor of 0.489 and the brand image factor of 0.803.